PENGUKURAN DAN EVALUASI KINERJA PERUSAHAAN PADA PT. ARTANIAGA MEGAH GEMILANG LECES PROBOLINGGO DENGAN MENGGUNAKAN BALANCE SCORECARD - Haris, R. Abdul; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2023)
Performance is a large part of the company's achievements and increases the company's survival. Performance measurement in 2019 dimensions are measured using Balanced Scorecard with four perspectives as dimensions. The four perspectives in question are: Finance, Customers, Internal Business, Learning and Growth as measuring tools for measuring and evaluating PT. Artaniaga Megah Gemilang Leces Probolinggo. The evaluation results obtained from the Financial Perspective achieved net profit performance still under control with an achievement of 98.90% or Rp. 1,575,179,805,- this is control incoming materials very good, the Internal Bistin Perspective has a good impact on the Financial Perspective and is supported by good human resource competence so that this perspective between plans and realization has very good achievements, the Customer Perspective is supported by a dominant learning and growth perspective with competence in accordance with plans especially training hours per person per year (JOB), and adequate employee productivity and competency, Learning and Growth supports two perspectives, namely the Internal Business Perspective and the Customer Perspective. With learning and growth, it is very important to achieve JOP, productivity, competency, all starting with good and programmed training. In closing, the results of measurement and evaluation between plan and realization were generally achieved, with the end of measurement in 2019 at the beginning of the Covid 19 pandemic, but the company's performance was still under control and achieved according to plan.